RANCANG BANGUN APLIKASI CUSTOMER TROUBLE SOLVING PADA PT INTI KARYA TEKNOLOGI BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER - Deslon Samosir (CKI ON SPOT, 2016)
System application to procces website improvement reported by client PT. Inti Karya Teknologi to IT Support Team only using email and no one program application has supported for this work process. In this study research author discussed analysis of the problem covered analysis of the problems of the system running the previous PT. Inti Karya Technology and provide a solution that can solve the problem that had occurred and to provide proposed new system, the process of analysis is done both in terms of IT Support Team at Work PT.Inti Technology and client PT Inti Karya Technology. The method used in this study using the method of observation and documentation as well as the author also uses UML (Unified Modeling Language) as Use Case Diagram, Activity Diagram, Sequence Diagram. Results to be achieved is by analyzing systems running earlier can be created an application that can be a container between IT Support and clients in the work process improvement website petition filed by the client and the process improvements made by the IT Support team more effective and efficient.Keywords: Website improvements, IT Support, Clients.